2007
DOI: 10.1126/science.1143991
|View full text |Cite
|
Sign up to set email alerts
|

Immune-like Phagocyte Activity in the Social Amoeba

Abstract: Social amoebae feed on bacteria in the soil, but they aggregate when starved and form a migrating slug that will undergo fruiting body morphogenesis to produce terminally differentiated spores and stalk cells. We describe a new cell type in the social amoeba which appears to provide detoxification and immune-like functions, which we term Sentinel (S) cells. S cells were observed to engulf bacteria and sequester toxins while circulating within the slug, eventually being sloughed off. A Toll/Interleukin-1 Recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
193
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(199 citation statements)
references
References 32 publications
3
193
0
3
Order By: Relevance
“…A recent study has revealed a further, unexpected, and quite remarkable anatomical feature of the slug (Chen et al 2007). The study identified cells scattered within the slug, the Sentinel cells (S cells), that phagocytose bacteria and sequester toxins.…”
Section: Developmental Markers and Prestalk And Stalk Cell Subtypesmentioning
confidence: 95%
“…A recent study has revealed a further, unexpected, and quite remarkable anatomical feature of the slug (Chen et al 2007). The study identified cells scattered within the slug, the Sentinel cells (S cells), that phagocytose bacteria and sequester toxins.…”
Section: Developmental Markers and Prestalk And Stalk Cell Subtypesmentioning
confidence: 95%
“…During development, a small population of phagocytic cells serves a protective roll to sequester toxic components. These 'sentinel' cells exhibit immune-like properties (Chen et al, 2007), and this might suggest a shared function of PS/-secretase in these cells and in mammalian macrophages.…”
Section: Phagocytosismentioning
confidence: 99%
“…The slug itself will not fall apart on encountering bacteria. Some shed cells are former sentinel cells, full of toxins and bacteria mopped up as they traversed through the slug (45).…”
Section: Dictyostelium Discoideum As a Model System For Cooperationmentioning
confidence: 99%